Hubungan Terpaan Kampanye 30 Hari Tanpa Minuman Manis dan Terpaan Berita Diabetes terhadap Perilaku Konsumsi Minuman Manis - Nurul Izzah, Saniyyah; Surayya Ulfa, Nurist; Luqman, Yanuar (Interaksi Online, 2024)
The high consumption level of sugar-sweetened beverages (SSB) among the public is a concerning issue that has become a hot topic of discussion. Indonesia ranks third in Southeast Asia for the highest consumption of SSB. One effort to reduce this high SSB consumption is the 30 Days Without Sugar-Sweetened Beverages Campaign. This campaign is a social media trend that challenges individuals to avoid consuming SSB for 30 days. Online media like Detik and Kompas are also striving to curb high SSB consumption in the community through news about diabetes caused by SSB consumption. This study aims to examine the correlation between the 30 Days Without Sugar-Sweetened Beverage Campaign exposure and diabetes news exposure on sugar-sweetened beverage consumption. The sample consisted of 100 respondents aged 18-35 years who had been exposed to information about the 30 Days Without SSB Campaign and diabetes news. The theory used in this study is the Theory of Reasoned Action (TRA). The sampling technique used is purposive sampling, and Kendall’s Tau_b test. The results show that the test value between the exposure to the 30 Days Without SSB Campaign and SSB consumption behavior has a significance value of 0.861, which is greater than 0.05, indicating that the correlation between the variables is not significant. The information and messages from the 30 Days Without Sugary Drinks Campaign received by the respondents cannot change their behavior in consuming sugary drinks but can only change their attitude towards SSB consumption. Similarly, the exposure to diabetes news and SSB consumption behavior has a significance value of 0.295, which is greater than 0.05, indicating that the correlation between the variables is not significant. This shows that the information and messages from diabetes news in online media cannot be the main factor causing a change in individuals' SSB consumption behavior. The study results indicate that there is no relationship between the two independent variables (campaign exposure and news exposure) and the dependent variable (sugary drink consumption behavior)